Studi Literature Review: Kajian Filologi terhadap Naskah Kuno Hadis di Indonesia - Ahmad Fauzi; Edriagus Saputra; Siti Suaibah; Ahmad Sapani; Ahmad Sahril; Siti Wardah; Arwansyah bin Kirin (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2026)
Ancient hadith manuscripts as an Islamic intellectual heritage in Indonesia reflect the dynamics of hadith transmission and adaptation in local contexts, but the increase in philological publications has not been accompanied by a comprehensive mapping of trends, methods, and scholarly contributions. This article answers the main question: how are publication trends, methodological approaches, and contributions to philological research on ancient hadith manuscripts in Indonesia developing, and what research gaps need to be addressed? The novelty of this research lies in a systematic literature review that integrates bibliometric analysis to uncover gaps such as the dominance of descriptive approaches and the lack of integration with classical hadith science. The methodology uses a qualitative literature review, a search of 30 articles via Google Scholar with the keyword